EVALUASI KELEMBAGAAN KEBIJAKAN KOTA LAYAK ANAK DI KOTA DEPOK - Nanang Saikhu; Ma’mun Murod; Khaerul Umam Noer (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2023)
Abstract. This study aims to analyze the institutional evaluation of the Policy for the Implementation of a Child Friendly City (KLA) in Depok City. The research background is that several institutional indicators have not been fulfilled in realizing KLA in Depok City. This research method uses a qualitative-descriptive approach with data collection techniques in the form of interviews, observation, and documentation studies. The public policy evaluation theory used is based on William N. Dunn's criteria, namely Effectiveness, Efficiency, Adequacy, Alignment, Responsiveness, and Accuracy. From the results of this study, the following conclusions were drawn: First, Effectiveness, institutional indicators of KLA policies have gone well with the formation of 11 sub-districts, 63 sub-districts, and 600 Child Friendly RWs. However, there are still several sub-districts and kelurahans that do not yet have Child-Friendly RWs and there are several Child-Friendly RWs that are not yet running well. Second, Efficiency, institutional support from the budgeting side is still inadequate, especially for sustainable programs. Third, Adequacy, KLA institutions have fulfilled adequacy but still needs to be improved further. Fourth, Alignment, KLA policy institutions have been evenly implemented by involving elements of the government, the business community, and the media. However, media participation is still not optimal. Fifth, Responsiveness, KLA institutions have received positive responses from implementers, such as regional apparatus organizations (OPD), the KLA Task Force, and the community. However, there are still implementers who do not understand much about KLA policies in Depok City so that it needs to beimproved further. Sixth, Accuracy, KLA policy institutions are considered to be on target and in accordance with KLA institutional indicators. However, it still needs further improvement in its implementation. Abstrak. Penelitian ini bertujuan untuk menganalisis evaluasi kelembagaan kebijakan Penyelenggaraan Kota Layak Anak (KLA) di Kota Depok. Penelitian dilatarbelakangi masih belum terpenuhinya beberapa indikator kelembagaan dalam mewujudkan KLA di Kota Depok. Metode penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan teknik pengambilan data berupa wawancara, observasi, dan studi dokumentasi. Adapun teori evaluasi kebijakan publik yang digunakan berdasarkan kriteria William N. Dunn, yaitu Efektivitas, Efisiensi, Kecukupan, Perataan, Responsivitas, dan Ketepatan. Dari hasil penelitian tersebut diperoleh kesimpulan: Petama, Efektivitas, indikator kelembagaan kebijakan KLA telah berjalan baik dengan terbentuknya 11 kecamatan, 63 kelurahan, dan 600 RW Ramah Anak. Namun, masih ada beberapa kecamatan dan kelurahan yang belum memiliki RW Ramah Anak dan ada beberapa RW Ramah Anak belum berjalan baik. Kedua, Efisieni, dukungan kelembagaan dari sisi penganggaran masih belum memadai, terutama untuk program berkelanjutan. Ketiga, Kecukupan, kelembagan KLA telah memenuhi kecukupan namun masih perlu ditingkatkan lagi. Keempat, Perataan, kelembagan kebijakan KLA telah merata dilakukan dengan melibatkan unsur pemerintah, masyarakat dunia usaha, dan media. Namun, partisipasi media masih belum optimal. Kelima, Responsivitas, kelembagaan KLA telah mendapat respon positif dari para pelaksana, seperti organisasi perangkat daerah (OPD), Gugus Tugas KLA, dan masyarakat. Namun, masih terdapat pelaksana yang belum banyak memahami kebijakan KLA di Kota Depok sehingga perlu ditingkatkan lagi. Keenam, Ketepatan, kelembagaan kebijakan KLA dinilai sudah tepat sasaran dan sesuai dengan indikator kelembagaan KLA. Namun, masih diperlukan peningkatan lebih lanjut dalam implementasinya.